2019
DOI: 10.1155/2019/2419096
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrocaffeic Acid Prevents UVB-Induced Oxidative Stress Leading to the Inhibition of Apoptosis and MMP-1 Expression via p38 Signaling Pathway

Abstract: Chronic UVB exposure promotes oxidative stress, directly causes molecular damage, and induces aging-related signal transduction, leading to skin photoaging. Dihydrocaffeic acid (DHCA) is a phenolic compound with potential antioxidant capacity and is thus a promising compound for the prevention of UVB-induced skin photodamage. The aim of this study was to evaluate the antioxidant and protective effect of DHCA against oxidative stress, apoptosis, and matrix metalloproteinase (MMP) expression via the mitogen-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 43 publications
1
37
0
1
Order By: Relevance
“…The human skin is prone to photoaging due largely to UV-induced excessive production of ROS. The effect is compounded by a concomitant depletion of the endogenous antioxidant system ( Shindo et al, 1994 ; Gęgotek et al, 2017 ; Oliveira et al, 2019 ) as a result of oxidative damage in cellular components ( Photoaging et al, 2019 ). Our results show that pre-treatment with nanoceria decreased L929 cells UVA-induced ROS production 24 h post-irradiation; with this effect persisting even after a further dose of UVA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The human skin is prone to photoaging due largely to UV-induced excessive production of ROS. The effect is compounded by a concomitant depletion of the endogenous antioxidant system ( Shindo et al, 1994 ; Gęgotek et al, 2017 ; Oliveira et al, 2019 ) as a result of oxidative damage in cellular components ( Photoaging et al, 2019 ). Our results show that pre-treatment with nanoceria decreased L929 cells UVA-induced ROS production 24 h post-irradiation; with this effect persisting even after a further dose of UVA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to UV rays induces the production of ROS by keratinocytes and immune cells [31,44]. For instance, ROS activate MAPK signaling pathway leading an increase in apoptosis of skin cells [45] and activate NF-κB signaling pathway leading to an increase in pro-inflammatory cytokine production such as IL-1β, TNF-α, and IL-6 [46]. These cytokines can activate vascular endothelial cells and contribute, therefore, to the recruitment of immune cells [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of NF-κB also regulates gp91 phox mRNA expression further increasing ROS production and inflammation [50]. Accordingly, treatment with PDTC (a NF-κB inhibitor) [30,51] or antioxidant molecules such as naringenin [52], dihydrocaffeic acid [45], and linalool [53] reduce UVB-induced NF-κB activation and oxidative stress, indicating a loop between ROS and this signaling pathway. Moreover, when phosphorylated, p65 NF-κB subunit competes with Nrf2 for the adaptor protein CREB binding protein (CBP) [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, researches focused on developing MMP inhibitors as antiphotoaging agents to prevent the UVB-induced degradation of the skin collagen [24,25]. Several studies reported very promising results indicating Evidence-Based Complementary and Alternative Medicine that ameliorating the MMP overexpression is a beneficial strategy against photoaging along with scavenging the UVBinduced ROS [26,27]. Keratinocytes form the main defense mechanism of skin against UVB irradiation as UVB rays mainly affect epidermis layer.…”
Section: Discussionmentioning
confidence: 99%